Assessing undertreatment and overtreatment/misuse of ADHD medications in children and adolescents across continents: A systematic review and meta-analysis - Massuti, Rafael; Moreira-Maia, Carlos Renato; Campani, Fausto; Sônego, Márcio; Amaro, Julia; Akutagava-Martins, Gláucia Chiyoko; Tessari, Luca; Polanczyk, Guilherme V.; Cortese, Samuele; Rohde, Luis Augusto (Neuroscience and biobehavioral reviews, 2021)
•A huge controversy exists on whether there is a pharmacological overtreatment or undertreatment of ADHD.•No previous study provides adequate data to inform this discussion.•Only 19.1 % of the ADHD diagnosed youths are being treated with medication for the disorder.•However, 0.9 % of all undiagnosed youth are also receiving pharmacological treatment.•Our estimative suggest that in the US there are 3 undertreated youths with ADHD for each potential mistreated case. A controversy exists on whether there is an over or underuse of medications for Attention-Deficit/Hyperactivity Disorder (ADHD). We conducted the first meta-analysis to estimate the rate of ADHD pharmacological treatment in both diagnosed and undiagnosed individuals. Based on a pre-registered protocol (CRD42018085233), we searched a broad set of electronic databases and grey literature. After screening 25,676 abstracts, we retained 36 studies including 104,305 subjects, from which 18 studies met our main analysis criteria. The pooled pharmacological treatment rates were 19.1 % and 0.9 % in school-age children/adolescents with and without ADHD, respectively. We estimated that for each individual using medication without a formal ADHD diagnosis, there are three patients with a formal diagnosis who might benefit from medication but do not receive it in the US. Our results indicate both overtreatment/misuse of medication in individuals without ADHD and pharmacological undertreatment in youths with the disorder. Our findings reinforce the need for public health policies improving education on ADHD and discussions on the benefits and limitations of ADHD medications.